2012
DOI: 10.1673/031.012.5501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Host Plants on Nutritional Indices of the Pod Borer,Helicoverpa armigera

Abstract: Nutritional indices of Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) on different host plants including chickpea (cultivars Arman, Hashem, Azad, and Binivich), common bean (cultivar Khomein), white kidney bean (cultivar Dehghan), red kidney bean (cultivar Goli), cowpea (cultivar Mashhad), tomato (cultivar Meshkin) and potato (cultivars Agria and Satina) were studied under laboratory conditions (25 ± 1 °C, 65 ± 5% RH, 16:8 L:D). Third instar larvae reared on potato Agria showed the highest efficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
53
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 36 publications
16
53
3
Order By: Relevance
“…The results for AD value of the whole larval instars reared on CH falat and Rio grande UG were different from those reported by Hemati et al (2012) on tomato var. Meshkin (67.470 ± 0.016%).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results for AD value of the whole larval instars reared on CH falat and Rio grande UG were different from those reported by Hemati et al (2012) on tomato var. Meshkin (67.470 ± 0.016%).…”
Section: Discussioncontrasting
confidence: 99%
“…A similar result was reported in numerous studies on H. armigera and other insects ( Barbosa and Greenblatt 1979 ; Naseri et al 2010 ; Arghand et al 2011 ; Hemati et al 2012) . Also, the results of whole larval instars showed that there is a negative correlation between RCR and ECI values.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The insects were kept in transparent plastic containers (10 × 5 × 5 cm) at 26±1°C, and a relative humidity (RH) of 65±5%. The photoperiod was 16 L : 8 D h (Hemati et al 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Although the modes of resistance or susceptibility of these arrays are not yet clear, it might be genotype based. Different nutritive values of host plants may also influence the rate of development of H. armigera larvae, thus affecting the population dynamics of this pest (Hemati et al, 2012). In spite of the pest hit in the season, there was an enhancement in yield when genotypes with resistance modes were planted.…”
Section: Discussionmentioning
confidence: 99%